Shear bond strength of self-adhering flowable composite on dentin surface as a result of scrubbing pressure and duration - Ferry Jaya; Siti Triaminingsih; Andi Soufyan S; Yosi Kusuma Eriwati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Self-adhering flowable composite is a combination of composite resin and adhesive material. Its application needs scrubbing process on the dentin surface, but sometimes it is difficult to determine the pressure and duration of scrubbing. Purpose: This study was aimed to analyze the effect of scrubbing pressure and duration on shear bond strength of self-adhering flowable composite to dentin surface Methods: Fifty four mandibulary third molar were cut to get the dentin surface and divided into nine groups (n = 6). Dentin surface was scrubbed with 1, 2, and 3 grams of scrubbing pressure, each for 15, 20, and 25 seconds respectively. surface was scrubbed with 1, 2, and 3 grams of scrubbing pressure, each for 15, 20, and 25 seconds respectively. Composite resin was applied incrementally and polymerized for 20 seconds. All specimens were immersed in saline solution at 37º C for 24 hours. Shear bond strength was tested for all specimens by using Universal Testing Machine (Shimadzu AG-5000E, Japan) at a crosshead speed of 1 mm/minute and analyzed by ANOVA and Post Hoc Test Bonferonni. The interface between self-adhering flowable interface between self-adhering flowable composite and dentin was observed with a Scanning Electron Microscope (JEOL JSM 6510LA). Results: The highest shear bond strength was obtained by 3 grams scrubbing pressure for 25 seconds or equal to applying the brush applicator in 0º relative to dentin surface. Conclusion: Increasing the scrubbing pressure and duration will increase the shear bond strength of self adhering flowable composite resin to dentinal surface. The highest shear bond strength was obtained when the applicator in 0º relative to dentin surface. Latar belakang: Self-adhering flowable composite merupakan gabungan resin komposit dengan material adhesif yang dalam penggunaannya memerlukan teknik scrubbing pada permukaan dentin, namun sulit untuk menentukan besar tekanan yang tepat saat scrubbing. Tujuan: Tujuan dari penelitian ini adalah untuk menganalisa pengaruh tekanan dan lama scrubbing saat aplikasi selfadhering flowable composite terhadap shear bond strength pada permukaan dentin. Metode: 54 gigi molar-3 rahang bawah dipotong sampai permukaan dentin dan dibagi atas 9 kelompok (n = 6). Scrubbing pada permukaan dentin dilakukan dengan besar tekanan 1, 2, dan Scrubbing pada permukaan dentin dilakukan dengan besar tekanan 1, 2, dan 3 gram, masing-masing selama 15, 20, dan 25 detik. Resin komposit diaplikasikan secara inkremental dan dipolimerisasi dengan sinar selama 20 detik. Spesimen direndam dalam larutan salin dan disimpan dalam inkubator pada suhu 37º C selama 24 jam. Shear bond strength diuji menggunakan Universal Testing Machine. Analisa data melalui uji ANOVA diikuti Post Hoc Test Bonferonni. Antarmuka self-adhering flowable composite resin dan dentin diamati melalui Scanning Electron Microscope (SEM). Hasil: Shear bond strength tertinggi antara self-adhering flowable composite resin dan dentin diperoleh pada tekanan scrubbing 3 gram selama 25 detik atau kuas membentuk sudut 0º dengan permukaan dentin. Kesimpulan: Semakin besar tekanan dan lama waktu scrubbing akan meningkatkan shear bond strength material self-adhering flowable composite resin terhadap permukaan dentin. Kekuatan paling tinggi diperoleh bila kuas aplikator membentuk sudut 0º dengan permukaan dentin selama proses scrubbing.